2015
DOI: 10.1021/acsami.5b04398
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Peroxidase/Oxidase Multiple Enzyme System Based on Supramolecular Hydrogel and Its Application as a Biocatalyst for Cascade Reactions

Abstract: Inspired by delicate structures and multiple functions of natural multiple enzyme architectures such as peroxisomes, we constructed an artificial multiple enzyme system by coencapsulation of glucose oxidases (GOx) and artificial peroxidases in a supramolecular hydrogel. The artificial peroxidase was a functional complex micelle, which was prepared by the self-assembly of diblock copolymer and hemin. Compared with catalase or horseradish peroxidase (HRP), the functional micelle exhibited comparable activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…23 Qu et al constructed a peroxidase/oxidase enzyme system based on a supramolecular hydrogel and investigated its application on cascade reactions as a biocatalyst. 24 Potier et al showed that the addition of methylated b-cyclodextrin in the supramolecular hydrogel could exert a positive effect on the catalytic activity of the hydroformylation reaction. 25 Guan et al reported the formation of a novel hydrogel via a host-guest complexation between PNIPAM and a cyclodextrin dimer, and the hydrogel responded sensitively to temperature, light, and reduction stimuli, in the form of a sol-gel conversion.…”
Section: Introductionmentioning
confidence: 99%
“…23 Qu et al constructed a peroxidase/oxidase enzyme system based on a supramolecular hydrogel and investigated its application on cascade reactions as a biocatalyst. 24 Potier et al showed that the addition of methylated b-cyclodextrin in the supramolecular hydrogel could exert a positive effect on the catalytic activity of the hydroformylation reaction. 25 Guan et al reported the formation of a novel hydrogel via a host-guest complexation between PNIPAM and a cyclodextrin dimer, and the hydrogel responded sensitively to temperature, light, and reduction stimuli, in the form of a sol-gel conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The value of K M for this reaction is 0.093 M. 27,28 The solutal expansion coefficient for oxygen (0.0014 M À1 ) 29 is an order of magnitude smaller than that for H 2 O 2 (0.011 M À1 ). Consequently, we neglect the contribution of O 2 to solutal buoyancy force in our calculations.…”
Section: Articlementioning
confidence: 86%
“…Since then, the number of such materials has been growing constantly. These include different material types, such as Nafion-cytochrome c [ 85 ], supramolecular complexes of hydrogel [ 86 ], nanocomplexes of lanthanides [ 87 , 88 , 89 , 90 , 91 , 92 ], Co 3 O 4 @CeO 2 hybrid microspheres [ 93 ], transition metal oxides and their composites [ 71 , 94 , 95 , 96 , 97 , 98 , 99 ], as well as noble metals: Au [ 100 ], Fe/Au [ 101 ], Au/Pt [ 102 ], Pt [ 103 , 104 ], Ru [ 105 ], Pt/Ru [ 60 ], Pd, Pd@Pt [ 106 ], Pd/Pt [ 107 ], Pd@γ-Fe 2 O 3 [ 108 ], etc. In the last decade, special interest in bionanotechnology has focused on the use of NZs based on carbon materials such as fullerenes [ 109 ], Prussian blue [ 110 ], TiO 2 [ 111 ] or Fe 2 O 3 /Pt-modified [ 112 ] multi-walled carbon nanotubes, hemin-graphene hybrid nanosheets [ 113 ], Pt/Ru/3D graphene foam [ 114 ], graphene oxide [ 115 ], Au/Pt/Au-graphene oxide nanosheets [ 116 ], Pd-magnetic graphene nanosheets [ 117 ], hemin-graphene-Au hybrid [ 118 ], IrO 2 [ 119 ], Cu-Ag [ 120 ] or Fe 2 O 3 -modified graphene oxide [ 121 ] ( Figure 4 ), Co-modified magnetic carbon [ 122 ], Co 3 O 4 graphene composite [ ...…”
Section: Nanozymes As Peroxidase Mimeticsmentioning
confidence: 99%